2007
DOI: 10.4141/p06-029
|View full text |Cite
|
Sign up to set email alerts
|

Effect of ammonium/nitrate ratio on growth and development of avocado plants under hydroponic conditions

Abstract: Lobit, P., López-Pérez, L., Cárdenas-Navarro, R., Castellanos-Morales, V. C. and Ruiz-Corro, R. 2007. Effect of ammonium/ nitrate ratio on growth and development of avocado plants under hydroponic conditions. Can. J. Plant Sci. 87: 99-103. An experiment was carried out to study the effects of the proportion of ammonium (NH 4 + ) and nitrate (NO 3 -) in the nutrient solution on avocado plants in a hydroponic system. Five treatments were applied, consisting of the following proportions of ammonium to nitrate ion… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
1
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 20 publications
(18 reference statements)
2
1
0
Order By: Relevance
“…Nitrate N was associated with induction of phytohormonal cascade transduction from root to shoot, leading to expansive leaf growth. This is in concurrence with findings of Lobit et al (2006), who found that a 49% reduction in the shoot length under dominant NH 4 + nutrition. These results were also in agreement with the findings of Gweyi- Onyango et al (2009) who observed a higher relative growth rate under nitrate even with lower concentrations as compared to ammonium.…”
Section: Plant Heightsupporting
confidence: 92%
“…Nitrate N was associated with induction of phytohormonal cascade transduction from root to shoot, leading to expansive leaf growth. This is in concurrence with findings of Lobit et al (2006), who found that a 49% reduction in the shoot length under dominant NH 4 + nutrition. These results were also in agreement with the findings of Gweyi- Onyango et al (2009) who observed a higher relative growth rate under nitrate even with lower concentrations as compared to ammonium.…”
Section: Plant Heightsupporting
confidence: 92%
“…These results are in agreement with those of Watson et al (1994) who reported delayed dissociation of urea to release N to a maximum period of 14 days depending on soil conditions resulting to low plant height. Other previous studies (Yong et al 2000;Lobit et al 2006;Borgognone et al 2013) also reported similar results of sharply reduced plant heights due to NH 4…”
Section: Plant Heightsupporting
confidence: 71%
“…Manthey & Crowley (1997) used 30 L hydroponic tank systems to test 'Hass' seedlings for physiological responses to Fe deficiency. Lobit et al (2007) andMiyasaka et al (1999) also successfully maintained avocado plants in hydroponic systems; however both of these studies employed the use of solid substrates to provide root system support. Use of such substrates for studies of avocado has the added benefit of in-built root system aeration.…”
Section: Discussionmentioning
confidence: 99%